Reinventing Jobs - Jesuthasan, Ravin; Boudreau, John (Ascent Audio, 2020)
Your organization has made the decision to adopt automation and artificial intelligence technologies. Now, you face difficult and stubborn questions about how to implement that decision: How, when, and where should we apply automation in our organization? Is it a stark choice between humans versus machines? How do we stay on top of these technological trends as work and automation continue to evolve? Work and human capital experts Ravin Jesuthasan and John Boudreau present leaders with a new set of tools to answer these daunting questions. Transcending the endless debate about humans being replaced by machines, Jesuthasan and Boudreau show how smart leaders instead are optimizing human-automation combinations that are not only more efficient but also generate higher returns on improved performance. Based on groundbreaking primary research, Reinventing Jobs provides an original, structured approach of four distinct steps-deconstruct, optimize, automate, and reconfigure-to help leaders reinvent how work gets bundled into jobs and create optimal human-machine combinations. Jesuthasan and Boudreau show leaders how to continuously reexamine what a job really is, and they provide the tools for identifying the pivotal performance value of tasks within jobs and how these tasks should be reconstructed into new, more optimal combinations.
Online resource; Title from title page (viewed November 3, 2020)
Keywords: Business; Affaires; Audiobooks